ANALISIS KAUSALITAS ANTARA KEMISKINAN, KETIMPANGAN PENDAPATAN DAN TINGKAT PENDIDIKAN DI PROVINSI SUMATERA BARAT - Damrul Ahmad; Mike Triani (Universitas Negeri Padang, 2018)
This study aims to determine and analyze the causal relationship between poverty, income inequality and education level in West Sumatra. This type of research is descriptive and associative research, where the data used is secondary data in the form of panel data from 2010 to 2017 with documentation data collection and literature study techniques obtained from related institutions and institutions. Data analysis used is the data used is descriptive analysis and inductive analysis. In inductive analysis there are several tests, namely: (1) Unit Root Test (2)Cointegration Test (3) Optimal Lag Determination (4) Granger Causality Test (5) PVAR Test. The results of this study indicate that (1) income inequality Poverty and income inequality have a causality relationship where the probability of poverty to income inequality = 0.0307 and the probability of income inequality against poverty = 0.0166 (2) There is a one-way relationship between poverty and education level where poverty affects the level of education with a probability = 0.0024 while the level of education does not affect poverty with probability = 0.2402 (3) income inequality and education level do not have a one-way or two-way relationship where income inequality does not affect the level of education with probability = 0, 2445 and the level of education also does not affect income inequality with a probability = 0.5248 in the study period. Based on the results of this study, the authors suggest that the government combine policies on income equity and poverty such as the application of progressive taxes and subsidies to basic needs, equitable distribution of education in districts / cities in regencies / cities in West Sumatra. in addition, it is also expected that an increase in the nine economic sectors so that all three issues such as poverty, income inequality and education levels can be overcome. Keyword: Poverty, Income Inequality, Education Level, PVAR